2016
DOI: 10.1155/2016/8341487
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and General and Abdominal Obesity in a Representative Sample of Spanish Adults: Findings from the ANIBES Study

Abstract: Objective. To analyze the anthropometric parameters from a representative sample of Spanish adults participating in ANIBES study and the prevalence of general and abdominal obesity. Methods. This cross-sectional study focused on 1655 adults aged 18–64 years. Weight, height, and waist circumference (WC) were evaluated, and body mass index (BMI) and waist to height ratio (WHtR) were calculated. A composite index combining BMI and WHtR was designed to establish five groups with different anthropometric status. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
3
7

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 45 publications
9
25
3
7
Order By: Relevance
“…Some of these results have been described in previous publications [2,19] and are presented again for simple characterization. The final sample consisted of 1655 individuals (48.2% men).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Some of these results have been described in previous publications [2,19] and are presented again for simple characterization. The final sample consisted of 1655 individuals (48.2% men).…”
Section: Resultsmentioning
confidence: 81%
“…The associations of sex and age with OW, OB and AO in the ANIBES study have been previously described [2]. It has been suggested that sex itself (sex hormones affect the amount and distribution of body fat) is a factor influencing body composition, its oxidation and mobilization [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En España se aprecia una tendencia creciente del número de personas con esta enfermedad, observándose en más de la mitad de la población obesidad abdominal (1).…”
Section: Introductionunclassified